Conservative Management of Placenta Percreta: Three Cases and a Review of the Literature regarding Conservative Management of Placenta Accreta Spectrum (PAS) Disorders. - M. Patabendige; J. M. P. Sanjeewa; A. M. A. K. G. Amarasekara; R. P. Herath (Hindawi Limited, 2020)
Background. The incidence of placenta accreta spectrum (PAS) disorders has risen over the last decades, and there has been a gradual shift towards expectant management. Conservative management of PAS is known to reduce major obstetric haemorrhage and salvage hysterectomy. There is a lack of consensus on the follow-up of patients undergoing conservative approaches. Here, we describe the follow-up of three patients with placenta percreta who were conservatively managed and review the literature for the conservative management of PAS. Case Presentation. We have successfully managed three cases of placenta percreta expectantly using combined methods involving symphysial-fundal height, serum beta-HCG, and ultrasonographic volume of placental mass. Conclusions. Use of a combined approach with symphysial-fundal height, serum beta-HCG, and ultrasonographic volume of placental mass with colour Doppler may guide the surveillance of these conservatively managed cases. However, at least one magnetic resonance imaging three months postoperatively may predict a further risk of delayed haemorrhage.